DETERMINAN PRODUKTIVITAS LAHAN PERTANIAN SUBSEKTOR TANAMAN PANGAN DI INDONESIA - Adhitya, Fazriyan Wardani; Hartono, Djoni; Awirya, Agni Alam (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2013)
This study is aimed to analyze the determinant factors affecting the agricultural land productivity of food crops sub-sectors in 25 provinces in Indonesia during the period of 2005-2009. Descriptive analysis is done to describe the agricultural land productivity of food crops sub-sectors in Indonesia. The Cobb-Douglas production function with the assumption of Constant Return to Scale on the food crops sub-sectors production is applied. To solve the heteroschedasticity problems and avoid the auto-correlation, then the Generalized Least Square estimator with Cross-Section Weight is done.The result shows that labors and fertilizer are two factors that do not affect significantly to the productivity of food crops sub-sectors; while capital, research, human resources and irrigation are factors that affect positively to the agricultural land productivity of food crops sub-sectors. The study also shows Java as the area with the highest level of productivity and Maluku has the lowest level of productivity.